Hadith Study of Morals: Praiseworthy and Disgraceful Behavior - Uus Husni Hoer; Robiatul Samiah; Ahmad Daud; Sarah Apiani; Zaki Rizanata (Taqriri: Journal of Al-Hadith Science Studies, 2025)
The word morality comes from the Arabic word khalaqu-yahluqu which etymologically means character, disposition, arrangement, behavior or nature. Morality is divided into two parts, namely commendable morality and reprehensible morality. Commendable morality itself has the meaning of eliminating reprehensible behavior that violates religious norms and adorning oneself with good deeds. While reprehensible morality has the meaning of actions that are not justified by religion (Allah and His Messenger). Morals play a very important role in everyday life, morality is a trait that is embedded in humans and can be of good or bad value, Morality is not always identical to knowledge, speech or actions of people who can know a lot about the good and bad of morality, but this is not necessarily supported by the nobility of morality, people can speak softly and sweetly, but words can come from a hypocritical heart. In other words, morality harms the innate human traits since birth that are embedded in their souls and are always there. The Qur'an always emphasizes that morality, whether good or bad, will reflect on oneself according to its formation and development. This journal traces the trail of noble morality in Islam by focusing on the concept of commendable and reprehensible behavior as stated in the hadith. Through an in-depth analysis of authentic hadiths, this study reveals various examples of commendable behavior such as honesty, trustworthiness, compassion, and patience, as well as reprehensible behavior such as lying, betrayal, envy, and arrogance. This journal concludes that understanding and practicing the concept of commendable and reprehensible behavior in the hadith is the main key in building individuals and societies with noble morals, and is an important guideline in dealing with various moral problems in the era of globalization.